Syndrome-based Approach to Diagnosis A Practical Guide - Benenson, Efim. (Springer London : Imprint: Springer, 2013)
Many young, inexperienced doctors, have difficultly pinpointing a diagnosis: Is it a condition to which certain diseases could belong, or a disease definable in line with certain criteria? How can I apply my basic knowledge of diseases to a real patient? How can I find the correct diagnosis for a disease that I am seeing for the very first time? The traditional diagnostic pathways conveyed by current methods of teaching, from visual identification of the disease, knowledge of diseases, understanding of symptoms or patterns to diagnosis, leave certain diagnostic questions unanswered, especially on first experience of such a clinical pattern. Syndrome-based Approach to Diagnosis: A Practical Guide offers lecturers an alternative training concept in their teaching, which provides students with a model for self-study as well as the educational tools for learning how to think in clinical terms. It also includes a basic structured program for internal medicine at a glance in the form of decision trees that cover all major internal medicine fields. This training concept is suitable as: ʺ A self-assessment test ʺ A study program (self study and case-based study) ʺ A basic program covering all the major teaching objectives in a clinical discipline ʺ A guideline and educational framework for differential diagnosis ʺ A collection of individual therapeutic options (with presentation of clinical cases) This book is a comprehensive educational tool ideal for medical professionals and those working within medical education.